Evaluation of bioherbicide for controlling weedy rice and enhancing the yield of rice in Malaysia - M.A. Hakim; A.S. Juraimi; N.B. Khalid; F. Aslani; Md Amirul Alam; S.M.R. Karim; A.K.M. Mosharof Hossain; M.S. Islam (2018)
Aim: Rice (Oryza sativa L.) is the second most important food crop in Malaysia, and weedy rice is the severe constraint in the Malaysian rice field. An experiment was conducted in Shadehouse at Field 2, Universiti Putra Malaysia to assess the performance of Agroplus BioDcomposer as a bioherbicide to control weedy rice and to select appropriate dosage of Agroplus BioDcomposer for effective control of weedy rice in the rice field.